Acculturation Level and Cultural Adaptive Strategies of Camp-Dwelling Biharis in Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
This study rambles on those ‘Bangladeshis’ who made mass people of Bangladesh contemplate for a long time whether ‘Bangladesh is for Bangladeshis or for Bangalis.’ This statement is sufficient for hinting that current research is on Urdu-Speaking Bangladeshi minor group who were the victims of political jumbles and helplessly migrated to present territory of Bangladesh after the partition of Indian subcontinent and hold a range of fundamental cultural heterogeneities with native Bengalis. The research aimed to investigate the acculturation level, cultural adaptation strategies and factors stimulating the acculturation process of camp-dwelling Biharis. In order to reach the objectives, mixed research methodology has been followed where composite indexing of numeric values and qualitative analysis of observation, narrative interviews and KIIs have been conducted. The study reveals that due to having social, cultural and ideological conflicts, Biharis have not been able to fully assimilate with the host community. Yet, they have managed to integrate with native Bengalis as indicated by composite index value of 0.53 through cultural learning, intermarriages, social interactions, legalizing political identity, entrance to labor force etc. Because of persisting discrimination, power conflict, prejudice and lack of peoplehood, they are still on the third stage of Gordon’s Model of Assimilation.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022, P 16-26